Toxicity evaluation of particles formed during 3D-printing: Cytotoxic, genotoxic, and inflammatory response in lung and macrophage models. (15th February 2022) - Vallabani, N.V. Srikanth; Alijagic, Andi; Persson, Alexander; Odnevall, Inger; Särndahl, Eva; Karlsson, Hanna L.
Graphical abstract: Abstract: Additive manufacturing (AM) or "3D-printing" is a ground-breaking technology that enables the production of complex 3D parts. Its rapid growth calls for immediate toxicological investigations of possible human exposures in order to estimate occupational health risks. Several laser-based powder bed fusion AM techniques are available of which many use metal powder in the micrometer range as feedstock. Large energy input from the laser on metal powders generates several by-products, like spatter and condensate particles. Due to often altered physicochemical properties and composition, spatter and condensate particles can result in different toxicological responses compared to the original powder particles. The toxicity of such particles has, however, not yet been investigated. The aim of the present study was to investigate the toxicity of condensate/spatter particles formed and collected upon selective laser melting (SLM) printing of metal alloy powders, including a nickel-chromium-based superalloy (IN939), a nickel-based alloy (Hastelloy X, HX), a high-strength maraging steel (18Ni300), a stainless steel (316L), and a titanium alloy (Ti6Al4V). Toxicological endpoints investigated included cytotoxicity, generation of reactive oxygen species (ROS), genotoxicity (comet and micronucleus formation), and inflammatory response (cytokine/chemokine profiling) following exposure of human bronchial epithelial cells (HBEC) or monocytes/macrophages (THP-1). The results showed no or minor cytotoxicity in the doses tested (10−100 μg/mL). Furthermore, no ROS generation or formation of micronucleus was observed in the HBEC cells. However, an increase in DNA strand breaks (detected by comet assay) was noted in cells exposed to HX, IN939, and Ti6Al4V, whereas no evident release of pro-inflammatory cytokine was observed from macrophages. Particle and surface characterization showed agglomeration in solution and different surface oxide compositions compared to the nominal bulk content. The extent of released nickel was small and related to the nickel content of the surface oxides, which was largely different from the bulk content. This may explain the limited toxicity found despite the high Ni bulk content of several powders. Taken together, this study suggests relatively low acute toxicity of condensates/spatter particles formed during SLM-printing using IN939, HX, 18Ni300, 316L, and Ti6Al4V as original metal powders.